CONCEIÇÃO DE MIL SAMBAS - Maia, Leandro (Paralelo 31, 2021)
Conceição Rosa Teixeira (1940-) compôs mais de mil sambas sem receber educação musical formal nem reconhecimento, oferecendo a oportunidade para entender processos criativos em música popular. O trabalho de Conceição Teixeira toca em questões de gênero, religião, classe e etnia a partir da perspectiva sociológica da produção cultural (BOURDIEU, 1993), articulando reflexões sobre habitus, campo e capital cancional.Palavras-chave: Habitus cancional; Aprendizagem informal; Música popular brasileira; Compositoras cancionistas. CONCEIÇÃO: WOMAN OF A THOUSAND SAMBASAbstract: Conceição Rosa Teixeira (1940-) wrote more than a thousand sambas without receiving formal musical education or recognition. She offers the opportunity to understand creative processes in popular music. Her work relates to issues of gender, religion, class and ethnicity from the sociological perspective of cultural production (BOURDIEU, 1993), articulating reflections on habitus, field and capital in songwriting. Keywords: Songwriting habitus; Informal learning; Brazilian popular music; Women songwriters.